Virus titer as a disease resistance indicator in tomato - Ali, Sajid; Fatima, Ammara; Khalid, Sana; Saeed, Farah; Shafiq, Muhammad; Afzaal, Sohaib; Haider, Muhammad Saleem; Tariq, Wajeeha; Khan, Jahangir (Bangladesh Journal of Botany, 2019)
Tomato leaf curl new Delhi virus, a geminivirus with a wide host range is a contagious pathogen of tomato, which also infects many other crops and weeds. Whitefly (Bemisia tabaci Gennadius), a polyphagous vector, is the agent responsible for its spread on a large scale. The pathogen is responsible for a major reduction in the yield of tomato. Ten commercial cultivars of tomato plant were selected to evaluate the effect of virus titer on crop yield. The yield potential along with other traits of these cultivars was assessed on the basis of symptom development, and virus DNA accumulation. The relationship between the virus titer, symptom severity, and agro-economic traits were established. The present results explain that the high level of virus accumulation in plant tissue results in the development of severe symptoms and leads to a major reduction in yield in case of susceptible cultivars, but this is not true for the cultivars showing intermediate resistance. The virus DNA remains low and approximately constant in resistant cultivars and has minimal effect on the yield and health of tomato.